1992
DOI: 10.1128/aem.58.5.1440-1446.1992
|View full text |Cite
|
Sign up to set email alerts
|

Pathovar-specific requirement for the Pseudomonas syringae lemA gene in disease lesion formation

Abstract: The lemA gene is conserved among strains and pathovars of Pseudomonas syringae. In P. syringae pv. syringae B728a, a causal agent of bacterial brown spot disease of bean, the lemnA gene is required for lesion formation on leaves and pods. Using lemA-containing DNA as a probe, we determined that 80 P. syringae pv. syringae strains isolated from bean leaves could be grouped into seven classes based on restriction fragment length polymorphism. Marker exchange mutagenesis showed that the lemA gene was required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In P. syringae pv. syringae, the lemA gene is required for the production of syringomycin, extracellular protease (25,40), and presumably other unidentified genes that are required for disease. In P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In P. syringae pv. syringae, the lemA gene is required for the production of syringomycin, extracellular protease (25,40), and presumably other unidentified genes that are required for disease. In P. syringae pv.…”
Section: Discussionmentioning
confidence: 99%
“…syringae B728a lemA gene (which will be designated hereafter lemA4p,) is contained within the insert of the plasmid pEMH97 and is required for disease symptoms on bean, as well as for the in vitro production of syringomycin and protease by P. syringae pv. syringae B728a (22,23,40,61). In addition, Southern blot analysis showed that pLEM57, the restoring subclone from the P. syringae pv.…”
Section: -Kbmentioning
confidence: 99%
“…Previous work had demonstrated that gacS (as lemA) was as important for the development of brown spot symptoms by a set of recent field isolates as it was for B728a (22). Three of these isolates were checked both for the ability to swarm and for the involvement of gacS in the swarming process.…”
mentioning
confidence: 99%
“…The gacA (for global antibiotic and cyanide control) gene was first described for Pseudomonas fluorescens as a regulator of production of a number of secondary metabolites that contribute to its biocontrol activity against a fungal root rot disease of tobacco (18). Homologs of lemA and/or gacA have since been identified in a number of pseudomonads, including other pathovars of P. syringae (1,27) and other species of Pseudomonas (4,7,17,20).…”
mentioning
confidence: 99%